Electron transfer kinetics on natural crystals of MoS2 and graphite1. Issue 27 (21st July 2015) - Velický, Matěj; Bissett, Mark A.; Toth, Peter S.; Patten, Hollie V.; Worrall, Stephen D.; Rodgers, Andrew N. J.; Hill, Ernie W.; Kinloch, Ian A.; Novoselov, Konstantin S.; Georgiou, Thanasis; Britnell, Liam; Dryfe, Robert A. W.
<x xml:space="preserve">Abstract</x> Electron transfer kinetics on MoS2 and graphite crystals are studied as a function of surface defectiveness, ageing, potential and illumination.